(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2025)
The paper analyzes the alternative negotiating instruments to the support administration, focusing, firstly, on the solutions provided by the current legal system, and, subsequently, on the prospects for reform of the Italian legal system, also in the light of the contiguous foreign experiences.